Physical oceanography during BALTICA cruise BALTI_062014 - Hans-Harald Hinrichsen; Adam Woźniczka; Andreas Lehmann (PANGAEA, 2025)
Conductivity-temperature-depth profiles were measured using a CTD. The CTD was equipped with duplicate sensors for temperature, conductivity and oxygen. All sensors are calibrated irregularly.
In: Hinrichsen, Hans-Harald; Reusch, Thorsten B H; Dierking, Jan; Lehmann, Andreas (2025): Timeseries of physical oceanography in the Baltic Sea from 2011-2022 [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.979407